Sasi as a Lingat Village Government Strategy for the Preservation of Taripang in the Tanimbar Islands - Yohekbet Dorkas Wally; Titus Gaite; Jumiati Tuharea (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Writing this thesis discusses "Village Government Strategy for the Preservation of Sasi Taripang in the Lingat Village Community, Selaru District, Tanimbar Islands Regency". The problems discussed in writing this thesis are: 1. government strategy and implementation in sasi dance 2. How is the sasi dance law implemented in the lingat village community 3. What is the role of the lingat village government in preserving sasi dance. The type of research used is descriptive qualitative research where the data is obtained through observation and interviews. The research location was carried out in Lingat Village, Selaru District, Tanimbar Islands Regency. Where the research subjects used in this study totaled 12 people including: 3 village government officials, 1 head of a traditional institution, 1 head of the Village Consultative Body (BPD), 1 entrepreneur, 5 community members, and the village head as an informant. The results of this study indicate that the village government strategy is a benchmark for the community to preserve existing natural resources, such as sasi taripang where this sasi law has existed for a long time and is passed on from generation to generation, and is continued by the role of the village government to preserve it through Lingat Village Regulation No 05/01/DSL/I/2021 "About sasi violations, and the time for carrying out sasi" and a fine of Rp. 1,000,000.00 as a form of strategy and the government's role in maintaining the preservation of sasi taripang so that it does not extinct.